Java-Moslem Family Communication Regarding Sexual and Reproduction Health Issue - Kusuma, Rina Sari; Muslimah, Rizky Azizah (Interaksi: Jurnal Ilmu Komunikasi, 2018)
The importance of sexual-content conversation between parents and children is still debatable. Especially in the eastern and Islamic culture that kind of communication still considered taboo. Parents' lack of awareness regarding their children’s knowledge of sexual and reproductive health urges children to find information from others, like peers and media. This lead to an increase in sexually transmitted infection, teen pregnancy, and abortion among young girls. This research wants to know how Java-Moslem parents communicate with their children about reproduction and sexual health issue. Using a qualitative approach, four families are interviewed to describe their belief and communication pattern regarding these issues. This resulted in parents and children's perception in seeing this issue as an embarrassing topic, so they engage in less self-disclosure. They talk implicitly with both parties had a mutual tendency to avoid open and direct communication. Javanese culture does have an enormous role in restricting and limiting this important issue to be discussed toward constructive and preventive conversation.